Navigating the Digital Frontier: An Examination of the Legal and Regulatory Framework for FinTech and Cryptocurrency in Nigeria - Nnebuihe, Linda Iheanacho; Ogu, Lorrita (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
The Nigerian FinTech ecosystem has emerged as one of the most vibrant on the African continent, driven by a large, young, tech-savvy population and a historical gap in traditional financial services. Concurrently, Nigeria has become a global epicenter for cryptocurrency adoption. However, this rapid innovation has occurred within a complex, often fragmented, and sometimes contradictory legal and regulatory environment. This paper provides a comprehensive examination of the multifaceted regulatory framework governing FinTech and cryptocurrencies in Nigeria. It analyzes the roles and sometimes conflicting directives of key regulatory bodies, including the Central Bank of Nigeria (CBN), the Securities and Exchange Commission (SEC), and the National Information Technology Development Agency (NITDA). The study employs a doctrinal methodology, critically analyzing primary sources such as statutes, regulatory circulars, and policy documents, supplemented by secondary sources including scholarly articles and industry reports. It identifies significant regulatory gaps, overlaps, and challenges, particularly concerning cryptocurrency bans, data privacy, and consumer protection. The paper argues that the current reactive and sometimes prohibitive stance stifles innovation and creates legal uncertainty. It concludes by proposing recommendations for a more cohesive, innovation-friendly, and forward-looking regulatory paradigm that balances the imperative of stimulating financial innovation with the critical need for market integrity, financial stability, and consumer protection.